Carbamazepine and Thyroid Hormones - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
Changes in serum thyroid hormone levels in 37 children with epilepsy receiving carbamazepine (CBZ) and valproic acid (VPA) were analyzed at the University of Chieti and University of Siena, Italy.